1986
DOI: 10.1002/neu.480170508
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intra‐axonal calcium distribution following nerve crush

Abstract: We used the oxalate-pyroantimonate method to demonstrate the ultrastructural distribution of calcium within rat sciatic nerve 4 h after a crush injury. In normal nerve there are discrete gradients of axoplasmic calcium precipitate with the amount of precipitate decreasing in the axoplasm beneath the Schmidt Lantermann clefts and in the paranodal regions at the node of Ranvier. Near the crush site a marked increase in endoneurial and intra-axonal calcium precipitate correlated with morphologic evidence of axona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…The vast majority of SLCs in the sciatic nerve display a characteristic calcium distribution profile along the axis of the axons, which was demonstrated with the same oxalatepyroantimonate technique as used in the present study (Mata et al, 1986(Mata et al, , 1987. The highest density values of the EDDs were detected outside the cleft, while minimal amounts or none were present just under the cleft, as illustrated in Fig.…”
Section: Classification Of the Schmidt-lanterman Clefts With Regard Tmentioning
confidence: 68%
See 1 more Smart Citation
“…The vast majority of SLCs in the sciatic nerve display a characteristic calcium distribution profile along the axis of the axons, which was demonstrated with the same oxalatepyroantimonate technique as used in the present study (Mata et al, 1986(Mata et al, , 1987. The highest density values of the EDDs were detected outside the cleft, while minimal amounts or none were present just under the cleft, as illustrated in Fig.…”
Section: Classification Of the Schmidt-lanterman Clefts With Regard Tmentioning
confidence: 68%
“…Using the oxalatepyroantimonate method to fix and identify calcium at the ultrastructural level, it was shown that in uninjured, wildtype axons there are discrete gradients of axoplasmic calcium that produce a characteristic pattern of precipitate, decreasing in the axoplasm beneath the Schmidt-Lantermann clefts (SLCs) and in the paranodal regions at the node of Ranvier (Mata et al, 1987). Within 4 h of nerve injury, long before any steady increase in total calcium levels, the uneven distribution of calcium precipitate below the majority of SLCs is lost (Mata et al, 1986).…”
Section: Introductionmentioning
confidence: 98%
“…22 In addition to primary and secondary injury, the concept of a tertiary phase of TBI may now be thought of as ongoing abnormalities in glucose utilization and cellular metabolism as well as membrane fluidity, synaptic function, and structural integrity. 3,35,[43][44][45]66,67,71,78 This phase of TBI may become chronic and compounded if the individual is subjected to repetitive minor head impacts.…”
Section: Laboratory Evidence Of Subconcussive Effectsmentioning
confidence: 99%
“…Axotomy causes a large increase of the free intracellular Ca 2ϩ concentration in the transected axon, mainly because of Ca 2ϩ influx through the cut end (Borgens et al, 1980;Happel et al, 1981;Mata et al, 1986;Strautman et al, 1990;Rehder et al, 1991Rehder et al, , 1992Spira, 1993, 1995). This influx forms a steep [Ca 2ϩ ] i gradient along the severed axon, in which Ca 2ϩ concentrations Ͼ1 mM are recorded near the cut end.…”
Section: Abstract: Growth Cone Formation; Axotomy; Calcium; Fura-2; mentioning
confidence: 99%